A Study of Kitten Behaviours in The Urban Backyard - Rosalia Rosalia; Teuku Reza Ferasyi; Nanda Yulian Syah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
Kitten is the earliest stage of a cat’s life, starting from 0 – 6 months old. As the golden age of a human baby in their first 1000 days of life, a kitten is the golden period for cats to grow and explore the environments. People tend to adopt cats at this stage as it is easier for them to shape and understand the characteristics of their cats. Therefore, understanding the behaviors of cats during the kitten period is fundamental. This study observed the behaviors of two pet kittens at 13 weeks of age when they roamed around the urban backyard. An ethogram was designed to record the duration of states (in second) and the frequency of events (per observation) of all behaviors. During the assessments, both kittens dominantly performed exploratory behaviors. They tended to explore the environment by sniffing ground, climbing trees, staring at birds, and walking around the backyard. These behaviors could be seen more often than their playing behaviors (object play and social play). In conclusion, this study supports the view that during the late socialization period (9-16 weeks), kittens seem to show the intense exploration of the environment as part of the development of predatory behavior or hunting skills in wild nature settings.